Production of the UVB-absorbing compound mycosporine-glutaminol-glucoside by Xanthophyllomyces dendrorhous (Phaffia rhodozyma) - Libkind Frati, Diego (2011)
The ability of the basidiomycetous yeast Xanthophyllomyces dendrorhous (Phaffia rhodozyma) to accumulate astaxanthin is responsible for the industrial use of this yeast as a microbial source of pigments for aquaculture. It is also hypothesized that astaxanthin accounts for its ability to thrive in highly oxidative and UV-exposed habitats. Here, we assessed the ability of this species to synthesize UV-absorbing compounds generally known as mycosporines, evaluated the effect of culture media in the production of these compounds and compared its UV growth resistance and tolerance with other yeasts. The 48 wild and collection strains screened were positive for mycosporines and a unique compound identified as mycosporine?glutaminol?glucoside (MGG) was detected. Thus, the ability of X. dendrorhous to produce MGG, as described here for the first time, is so far unique among the Cystofilobasidiales. The compound was synthesized constitutively, although growth under visible light and, to a greater extent, UVA radiation stimulated its production. Strains from UV-exposed habitats produced larger quantities and oligotrophic complex media seemed to favor MGG accumulation. UV tolerance and survival of X. dendrorhous was high and comparable to that of the polyextremophilic Rhodotorula mucilaginosa. The taxonomical and ecological implications of the production of MGG by X. dendrorhous are discussed.